The 5 C model and Mpox vaccination behavior in Germany: a cross-sectional survey - Philip Oeser; Julianna Grune; Jendrik Dedow; Wolfram Joachim Herrmann (BMC, 2024)
Abstract Background Due to the authorization of the Mpox vaccines, we aimed to identify determinants of the intention to get vaccinated, actively trying to receive vaccination, and for successfully receiving a vaccination in Germany employing the 5 C model of vaccination readiness. Methods Data stem from a cross-sectional online survey that was available online from August 13, 2022 to August 31, 2022. To assess the influence of the 5 C Model on vaccination behavior, we conducted a multinomial logistic regression. Results 3,338 participants responded to the survey, with 487 already vaccinated and 2,066 intending to receive a vaccination. Confidence and collective responsibility were positively associated with intention to get vaccinated, while complacency was negatively correlated. A higher score on the calculation scale increased the odds of intention to receive vaccination but not with actively having tried to receive a vaccination. Fewer perceived constraints were associated with higher odds to be vaccinated. Patients in practices that focus on HIV treatment were more likely to intend to get vaccinated, to have tried to get vaccinated and to be vaccinated, regardless of indication. While level of education had no impact, having an indication to get vaccinated was a strong predictor of vaccination behavior in all groups. Conclusion Future vaccination campaigns should aim to reduce specific constraints of the target group and make vaccines widely available in primary care institutions beyond HIV-focused practices.